Social advertising as a tool of social marketing and a way to form a positive brand image - Agalarova, Karina; Zemliakova, Olena; Miroshnik, Maria; Kitchenko, Olena; Mironenko, Nadezda; Reshetniak, Natalia; Kuzmenko, Oleksandr (Akademické sdružení MAGNANIMITAS, Czech Republic, 2022)
The relevance of the study of social advertising as one of the streams of mass media focused on the humanization of public relations, which some authors even call the “information branch of social work”, increases as the reforms taking place in many countries increase their social content. The fact is that the stabilization of political life, an increase in the efficiency of the economy, and successful administrative and legal reforms are accompanied, unfortunately, by crisis phenomena in the social sphere, including the following: a deterioration in the demographic situation, a fall in moral and ethical values, and excessive stratification in property, incomes, access to healthcare services, etc.. In these conditions, social advertising becomes the most important factor in optimizing the process of social development in the public mind. At the same time, social advertising, designed to generate the creation and dissemination of socially significant values, acts as an essential element of information support for a civil society that is developing with great difficulties, at the same time bringing practical benefits to companies which are practicing social advertising in the framework of social PR and CSR programs.
Keywords: brand; CSR; social advertizing; social PR; sustainable development